ComWΔ6 Stimulates Transcription of Pneumococcal Competence Genes in vitro - Inniss, Nicole L.; Morrison, Donald A. (Frontiers in Molecular Biosciences, 2020)
The alternative streptococcal σ-factor and master competence regulator, σX, stimulates transcription from competence promoters, in vitro. As the only known alternative σ-factor in streptococci, σX expression is tightly controlled in each species and has a specific physiological role. Pneumococcal transformation also requires the DNA binding activity of ComW, a known σX activator and stabilizer. Mutations to the housekeeping σ factor, σA, partially alleviate the ComW requirement, suggesting that ComW is a key player in the σ factor swap during the pneumococcal competence response. However, there is no evidence of a direct ComW – RNA polymerase interaction. Furthermore, if and how ComW functions directly at combox promoters is still unknown. Here we report that a DNA-binding ComW variant, ComΔ6, can stimulate transcription from σX promoters in vitro.